2013
DOI: 10.1111/iju.12242
|View full text |Cite
|
Sign up to set email alerts
|

Nocturia Quality‐of‐Life questionnaire is a useful tool to predict nocturia and a risk of falling in Japanese outpatients: A cross‐sectional survey

Abstract: Abbreviations & Acronyms BPH = benign prostatic hyperplasia CI = confidence interval N-QOL = Nocturia Quality-of-Life questionnaire OAB = overactive bladder OAB-q = overactive bladder questionnaire OABSS = overactive bladder symptom score QOL = quality of life ROC = receiver operating characteristic Objectives: To evaluate the Japanese version of the Nocturia Quality-of-Life questionnaire for prediction of night-time voiding and risk of falling. Methods: A survey was carried out from October 2008 to June 2009 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
5
6
0
Order By: Relevance
“…Similar findings were observed in a study with adults, showing that nocturia was present in 70.4% of cases (16) , and a study of men with nocturia complaints showed that 12.0% woke up once during the night to urinate; 21.7%, twice; 28.4%, three times; 26% four times; and 11.3%, five times (17) . In the present study, nocturia was identified as the need to wake up more than once to urinate during the nighttime.…”
Section: Discussionsupporting
confidence: 87%
“…Similar findings were observed in a study with adults, showing that nocturia was present in 70.4% of cases (16) , and a study of men with nocturia complaints showed that 12.0% woke up once during the night to urinate; 21.7%, twice; 28.4%, three times; 26% four times; and 11.3%, five times (17) . In the present study, nocturia was identified as the need to wake up more than once to urinate during the nighttime.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, we used a nocturia‐specific quality of life questionnaire, N‐QoL, which was firstly described by Abraham et al 25 and we found that increased severity of nocturia was associated with impaired QoL of patients in concordance with previous studies 5,25 . Zhang et al evaluated the prevalence and risk factors of nocturia and nocturia‐related QoL in Chinese population with 1198 adults 26 . They also used the N‐QoL questionnaire and they reported that increasing episodes of nocturia and decreasing total sleeping hours were independent factors predicting a significantly lower N‐QOL score.…”
Section: Discussionsupporting
confidence: 65%
“…5,25 Zhang et al evaluated the prevalence and risk factors of nocturia and nocturia-related QoL in Chinese population with 1198 adults. 26 They also used the N-QoL questionnaire and they reported that increasing episodes of nocturia and decreasing total sleeping hours were independent factors predicting a significantly lower N-QOL score. Also, they noted that two or more nocturia episodes were associated with worse N-QoL scores as we did.…”
Section: Discussionmentioning
confidence: 99%
“…We attempted to evaluate the changes in nocturia-related QoL using the N-QoL questionnaire, which has been confirmed to be a useful tool for the evaluation of nocturia in Japanese patients [14]. The N-QoL Q7 score (inadequate sleep at night) and N-QoL Q12 score (overall bother) improved significantly after treatment with tadalafil (Tables 2, 3).…”
Section: Discussionmentioning
confidence: 99%